Development of technology for consolidation and synchronization of data of industrial-purpose integrated automated systems - Трейтяк, Вячеслав Віталійович (Eastern-European Journal of Enterprise Technologies, 2015)
The technology for synchronization and consolidation of production data of industrial-purpose integrated automated systems was developed. The technology is the architectural concepts of constructing and using a single consolidated information environment of the industrial enterprise. The functioning of a single consolidated environment occurs via the central link - a single integrated automated system that performs the functions of management of integration and exchange of data between various production systems. For "correct" presentation of data in various integrated automated systems, the mathematical model of production data transformation in a single intermediate format, which uses data transformation templates and establishes links between objects in these industrial-purpose systems was developed. Using a single consolidated environment provides information support of administrative decision-making on the major life cycle stages of the product. This support is based on presenting credible and operational design, production, planning and reference data used by various integrated automated systems in various departments and services of industrial enterprises. The research results as the basis for the integration methodology of automation processes of technical training, planning and operations management.